Structure, CO-releasing property, electrochemistry, DFT calculation, and antioxidant activity of benzimidazole derivative substituted [Mn(CO)3(bpy)L]PF6 type novel manganese complexes - Üstün, E.; Çol Ayvaz, M.; Sönmez Çelebi, M.; Aşci, G.; Demir, S.; Özdemir, I. (2016)
Metal carbonyl complexes are prominent group organometallic compounds because of their applications in industrial and pharmaceutical chemistry. In recent years, metal carbonyl complexes have been accepted major for storage and transportation of carbon monoxide which is an important signaling molecule significantly in pathogenesis of some diseases. Thus, we designed and synthesized novel manganese(I)carbonyl complexes with general formula [Mn(CO)3(bpy)L]PF6 (bpy = 2,2-bipyridyl, L = N-(2-chlorobenzyl)benzimidazole, N-(2-methoxybenzyl)benzimidazole, N-(2-methylbenzyl)benzimidazole). The complex molecules were characterized by LC-MS, 1H-NMR, 13C-NMR, IR spectroscopy methods and elemental analysis. The CO-releasing properties, antioxidant activities and redox properties of these complexes were investigated. The DFT/TDDFT analyses were made by ORCA package program. © 2016 Elsevier B.V.